Upon a starlit tide - Woods, Kell (Tom Doherty Associates/Tor Publishing Group, 2025)
"Saint-Malo, Brittany, 1758. To Lucinde Leon, the youngest daughter of a wealthy French shipowner, the high walls of Saint-Malo are more hindrance than haven. While her sisters are busy trying to secure advantageous marriages, Luce spends her days secretly being taught to sail by Samuel, her best friend--and an English smuggler. Only he understands how the waves call to her. Then one stormy morning, Luce rescues a drowning man from the sea. Immediately drawn in by the stranger's charm, Luce is plunged into a world of glittering balls and faerie magic, seduction and brutality. Secrets that have long been lost in the shadowy depths of the ocean begin to rise to the surface, but as Luce wrestles with warring desires, she finds that her own power is growing brighter and brighter, shining like a sea-glass slipper--or the scales of a sea-maid's tail."--